Perancangan antarmuka aplikasi foodCare menggunakan metode user centered design - Putro Setyoko (Universitas Muhammadiyah Riau, 2024)
Sustainable Development Goals (SDGs) is a global development plan that aims to eradicate poverty, reduce inequality and preserve the environment. FoodCare application design solutions or Mobile-based free food sharing applications are rare, although they only existed about a few years ago. The development of foodCare application design solutions generally focuses on the role of users or donors. The purpose of developing a foodCare app design solution is to help donors who want to voluntarily donate their excess food. Application usability is an important component of the application, which indicates how easy it is for users to use it. For this reason, this research was conducted to design the application interface in terms of user needs. The method used is User Centered Design (UCD) while the usability measurement uses the System Usability Scale (SUS) involving 14 respondents. The results of measuring the usability of foodCare using SUS are 85.35 with the Best Imaginable rating and are in grade A. These results indicate that designing foodCare application design solutions with the User Centered Design method can present a new solution that can help meet the needs of users.